2015
DOI: 10.1093/pch/20.4.189
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in long-term survivors of paediatric liver transplantation

Abstract: The self-reported HRQOL of participants <18 years of age was comparable with a standardized healthy population. In contrast, participants between 18 and 25 years of age had HRQOL scores that were more similar to a group with chronic illness. Participants engaged in full-time work/study experienced enhanced physical health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 29 publications
1
43
0
Order By: Relevance
“…SF‐36 domain scores are provided in Table . Two studies using the SF‐36 reported physical component scores as the lowest of the domain scores . In contrast, Kosola et al reported physical component scores to be the highest of all domain scores at 92.7 ± 12.3, higher than published US population norms (84.0 ± 23.0).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…SF‐36 domain scores are provided in Table . Two studies using the SF‐36 reported physical component scores as the lowest of the domain scores . In contrast, Kosola et al reported physical component scores to be the highest of all domain scores at 92.7 ± 12.3, higher than published US population norms (84.0 ± 23.0).…”
Section: Resultsmentioning
confidence: 86%
“…Kosola et al also reported school functioning scores to be comparable to other domains in patients <7 years old (79.8 ± 10.6), but the lowest of all domains (69.2 ± 15.7) in patients aged 7‐17 years. Two studies reported social functioning domain scores to be the highest of the reported scores. Table summarizes studies using the PedsQL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this systematic review show that PROMs are being used in the field of pediatric solid organ transplant . However, researchers advise that both generic and disease‐specific instruments are used to conduct a comprehensive evaluation of health status and overall QOL to generate more accurate depictions of a patient's health‐related QOL . In 52 out of 62 pediatric transplantation articles reviewed in this study, a second disease‐specific PROM was not administered in conjunction with a generic instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplantation is well‐established in Canada as the optimal standard of care for children experiencing end‐stage liver failure . Transplantation, as a treatment for pediatric end‐stage liver failure, has advanced long‐term health outcomes with ten‐year survival rates reaching 75%‐85% .…”
Section: Introductionmentioning
confidence: 99%